IMPROVING WRITING SKILL THROUGH RESEARCH-BASED INSTRUCTION (ResearchJet Journal of Analysis and Inventions, 2021)
Writing is multifaceted and includes a number of skills that must work together. Recent reviews of research have gathered what we know about effective practices to teach writing. Writing Next (Graham & Perin, 2007), and a companion analysis, What We Know, What We Still Need to Know (Graham & Perin, 2007), examine the research on writing instruction in grades 4-12, with attention given to those whose writing skills need improvement.